2016
DOI: 10.1371/journal.pone.0154531
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Senescence Associated Genes and Pathways in Primary Human Fibroblasts Detected by RNA-Seq

Abstract: Cellular senescence correlates with changes in the transcriptome. To obtain a complete view on senescence-associated transcription networks and pathways, we assessed by deep RNA sequencing the transcriptomes of five of the most commonly used laboratory strains of human fibroblasts during their transition into senescence. In a number of cases, we verified the RNA-seq data by real-time PCR. By determining cellular protein levels we observed that the age-related expression of most but not all genes is regulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 143 publications
18
82
0
Order By: Relevance
“…It is noteworthy that the common senescence markers, CDKN2A , CDKN1A , and LMNB1 , were not within the core signature, supporting the idea that known senescence markers lack universality for different cell types and inducers of senescence [10]. Indeed, one of the studies used here [14] showed that p16INK4A mRNA levels are not always significantly changed in senescence in some fibroblast strains. Although RNA levels do not always reflect protein levels, p16INK4A expression is often used as a senescence marker.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…It is noteworthy that the common senescence markers, CDKN2A , CDKN1A , and LMNB1 , were not within the core signature, supporting the idea that known senescence markers lack universality for different cell types and inducers of senescence [10]. Indeed, one of the studies used here [14] showed that p16INK4A mRNA levels are not always significantly changed in senescence in some fibroblast strains. Although RNA levels do not always reflect protein levels, p16INK4A expression is often used as a senescence marker.…”
Section: Resultssupporting
confidence: 61%
“…However, the second and third principal components separated the cells according to senescence status, with some influence from the study/dataset of origin (Figure S1A). Nonetheless, one sample within one of the datasets (RS IMR90 [14]) clustered differently from its replicates. The aberrant clustering of this sample was reported in the original study, and this sample was then removed from further analysis (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to deep quiescence, senescence and aging are at least partially driven by ROS and can be counteracted by the lysosome-autophagy pathway 6,8,18,19,36 . With this mechanistic similarity in mind, it was still striking to us that QDS correctly predicted cellular senescence and aging in a wide array of cell lines in vitro 21,22 and tissues in vivo 23,24 (Fig. 6b-d).…”
Section: Quiescence Deepening Parallels Cellular Senescence and Agingmentioning
confidence: 83%
“…We show that lysosomal function, like a dimmer switch, continuously regulates quiescence depth and thus the proliferative potential of quiescence cells, by reducing the accumulation of intracellular reactive oxygen species (ROS). Furthermore, we found that a gene expression signature developed by comparing deep and shallow quiescent REF cells was able to correctly classify senescent and aging cells in a wide array of cell lines in vitro 21,22 and tissues in vivo 23,24 , suggesting the existence of shared regulatory mechanisms underlying these cell fates and a possible sequential transition from shallow to deep quiescence and eventually to irreversible senescence that may contribute to aging.…”
Section: Introductionmentioning
confidence: 92%
“…For example, increased expression of genes involved in stress response and oxidative damage is observed in aging human brain, retina, skin and fibroblasts (Table 1) [26, 27, 30, 32, 53]. Similarly, genes involved in stress response and inflammation show increased expression with age in rodent brain, kidney, liver, muscle, and pancreatic cells, and in fruit flies [34, 37, 39, 54].…”
Section: What Types Of Genes Show Age-associated Changes In Expression?mentioning
confidence: 99%